The Effect of Using Virtual Laboratories Using the Guided Discovery Learning Model on Students' Conceptual Understanding of Static Electricity Material - Haeratunisah; Aris Doyan; Muhammad Taufik (Postgraduate, University of Mataram, 2024)
This study aims to test or examine the effect of the use of virtual laboratories using the Guided Discovery Learning model on students' conceptual understanding abilities in static electricity material. This type of research is a quasi-experimental study with a nonequivalent control group research design. The population in this study were all students of class XII of SMAN 1 Monta. The sampling technique used in this study was purposive sampling with class XII MIPA 2 consisting of 28 students as the experimental class and class XII MIPA 1 consisting of 28 students as the control class. Before and after the treatment, both classes were given a conceptual understanding ability test in the form of essay questions that had previously been tested for their feasibility with validity, reliability, difficulty level of questions, and discriminatory power. The results of the initial test (Pretest) and final test (Posttest) of conceptual understanding ability were analyzed for homogeneity and normality to conduct a hypothesis test. The analysis of the hypothesis test using the t-test obtained a t_count of 3.49 and a t_table of 2.00. Thus, the calculated t_value is greater than the t_table, so H_0 is rejected and H_a is accepted, so it can be concluded that there is an influence of the use of virtual laboratories using the Guided Discovery Learning model on students' conceptual understanding abilities in static electricity material.